Several Factors of Library Publishing Services Facilitate Scholarly Communication Functions - Bussert, Leslie (Evidence Based Library and Information Practice, 2012)
Objective – To identify and examine the factors of library publishing services that facilitate scholarly communication. Design – Analysis of library publishing service programs. Setting – North American research libraries. Subjects – Eight research libraries selected from the signatories for the Compact for Open-Access Publishing Equity (COPE) Cornell University Library’s Center for Innovative Publishing; Dartmouth College Library’s Digital Publishing Program and Scholars Portal Project; MIT Libraries’ Office of Scholarly Publishing and Licensing; Columbia University Libraries’ Center for Digital Research and Scholarship; University of Michigan Library’s Scholarly Publishing Office; Duke University Library’s Office of Scholarly Communications; University of Calgary Libraries and Cultural Resources’ Centre for Scholarly Communication; and Simon Fraser University Library’s Scholarly Publishing. Methods – The authors used Roosendaal and Geurt’s (1997) four functions of scholarly communication to analyze and categorize library publishing services provided by libraries included in the study. The four functions of scholarly communication include registration, certification, awareness, and archiving. Main Results – Analysis of the registration functions provided by library publishing services in this study revealed three types of facilitating factors: intellectual property, licensing, and publishing. These include services such as repositories for digital scholarly work and research, ISBN/ISSN registration, and digital publishing. Analysis of archiving functions demonstrated that most programs in the study focus on repository-related services in support of digital content preservation of papers, datasets, technical reports, etc. Analysis of certification functions provided by these services exposed a focus on expert review and research support. These include services like professional assessment of information sources, consultation on appropriate literature and information-seeking tools, and writing or copyright advisory services. Analysis of awareness function showed search aids and knowledge-sharing platforms to be the main facilitating factors. These include services like metadata application, schema, and standards or scholarly portals enabling knowledge-sharing among scholars. Conclusion – This study identified several services offered by these library publishing programs which can be categorized as facilitators under Roosendaal and Geurt’s (1997) four functions of scholarly communication. The majority of the libraries in the study treated library publishing services as part of broader scholarly communication units or initiatives. Digital publishing (registration function) was offered by all programs analyzed in the study, while traditional peer-review services (certification function) were not. Widely adopted among programs in the study were the use of social networking tools (awareness function) and self-publishing (archiving function). The authors recommend developing services that facilitate peer review and assert the need to provide a knowledge-sharing mechanism within the academic community that facilitates the scholarly communication process.